Human hepatocellular carcinomas with a periportal phenotype have the lowest potential for early recurrence after curative resection. Issue 5 (26th September 2017) - Désert, Romain; Rohart, Florian; Canal, Frédéric; Sicard, Marie; Desille, Mireille; Renaud, Stéphanie; Turlin, Bruno; Bellaud, Pascale; Perret, Christine; Clément, Bruno; Lê Cao, Kim‐Anh; Musso, Orlando
Abstract : Hepatocellular carcinomas (HCCs) exhibit a diversity of molecular phenotypes, raising major challenges in clinical management. HCCs detected by surveillance programs at an early stage are candidates for potentially curative therapies (local ablation, resection, or transplantation). In the long term, transplantation provides the lowest recurrence rates. Treatment allocation is based on tumor number, size, vascular invasion, performance status, functional liver reserve, and the prediction of early (<2 years) recurrence, which reflects the intrinsic aggressiveness of the tumor. Well‐differentiated, potentially low‐aggressiveness tumors form the heterogeneous molecular class of nonproliferative HCCs, characterized by an approximate 50% β‐catenin mutation rate. To define the clinical, pathological, and molecular features and the outcome of nonproliferative HCCs, we constructed a 1, 133‐HCC transcriptomic metadata set and validated findings in a publically available 210‐HCC RNA sequencing set. We show that nonproliferative HCCs preserve the zonation program that distributes metabolic functions along the portocentral axis in normal liver. More precisely, we identified two well‐differentiated, nonproliferation subclasses, namely periportal‐type (wild‐type β‐catenin) and perivenous‐type (mutant β‐catenin), which expressed negatively correlated gene networks. The new periportal‐type subclass represented 29% of all HCCs; expressed a hepatocyte nuclear factor 4A–driven gene network, which was down‐regulated in mouse hepatocyte nuclear factor 4A knockout mice; were early‐stage tumors by Barcelona Clinic Liver Cancer, Cancer of the Liver Italian Program, and tumor–node–metastasis staging systems; had no macrovascular invasion; and showed the lowest metastasis‐specific gene expression levels and TP53 mutation rates. Also, we identified an eight‐gene periportal‐type HCC signature, which was independently associated with the highest 2‐year recurrence‐free survival by multivariate analyses in two independent cohorts of 247 and 210 patients. Conclusion: Well‐differentiated HCCs display mutually exclusive periportal or perivenous zonation programs. Among all HCCs, periportal‐type tumors have the lowest intrinsic potential for early recurrence after curative resection. (Hepatology 2017;66:1502–1518).